Catastrophic Progressive Hearing Loss in Childhood - Hayes, Deborah; Dreith, Susan (Journal of the American Academy of Audiology, 2000)
We present a report on a 5-year-old child with a complex medical and audiologic history who exhibited catastrophic progression in hearing loss. Hearing loss was initially attributed to bacterial meningitis at age 3 months; progression was apparently related to perilymph fistula at age 8 years. Etiologies associated with progressive hearing loss in children as well as signs of progression and monitoring protocols for children at risk for progressive hearing loss are discussed.Abbreviations: ABR = auditory brainstem response, CMV = cytomegalovirus, JCIH = Joint Committee on Infant Hearing, LVA = large vestibular aqueduct, PPHN = persistent pulmonary hypertension of the newborn, TCH = The Children's Hospital
Keywords: Cytomegalovirus; hearing loss; meningitis